Pengembangan Sistem Keterbukaan Informasi - Pranidhana, G. Langgeng (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2018)
Regional Organizational Organization (OPD) is an organization or institution in the Regional Government that is responsible to the Regional Head in the framework of implementing governance in the region. Regional equipment is formed by each region based on consideration of the characteristics, potential and needs of the region. One of the obligations of the public body stated in Law No. 14 of 2008 is to provide a Public Information List (DIP). DIP is a record that contains systematic information about public information that is under the control of a public body. For this reason, facilities that can be used as a place for disseminating information on an information system can facilitate the dissemination of information both in terms of OPD devices and community users. The purpose of this research is to create an Information Disclosure System (SIKI) to assist and facilitate the publication process and the provision of public information from the Provincial Government of Bali to the community starting from the needs analysis process, design to implementation and testing of the system.